Strategi Pengelolaan Kelas dalam Meningkatkan Mutu Pembelajaran Fiqih di MDT Al-Munjiyat Pontianak - Abdul Pandi; Adim, Saiful; Khairul; Sholihin; Syafi’I; Samsuddin; Gusmi; Fadilah, Siti; Wulan, Nawang; Fitriani; Ilmiah, Putri Khairil; Rumiyatun (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This study aims to identify the factors that support and hinder classroom management strategies and evaluate the effectiveness of these strategies in enhancing the quality of learning. The research methodology employed is descriptive in nature and adopts a qualitative approach. The primary data sources consist of interviews, observations, and documentation obtained from school principals, teachers, and staff members. Secondary data sources include relevant journals, books, and websites. The data analysis entails data display, data reduction, and drawing conclusions. The findings of the study reveal the following: 1) Teachers employ various strategies in classroom management such as maintaining a positive classroom atmosphere, adopting personal approaches towards students, organizing seating arrangements, providing individual attention, and offering constructive warnings. These efforts significantly contribute to improving the learning process and outcomes. 2) The supporting factors for effective classroom management strategies encompass the availability of adequate facilities, a relevant school curriculum, teachers' abilities and competencies, a conducive learning environment, collaborative interactions among teachers, school administrators, and principals, an efficient school management system, and a strong teacher-student rapport. 3) Teachers also employ strategic initiatives in classroom management, including the provision of school facilities, the inclusion of Quranic reading prior to lessons, the enhancement of teacher competence, self-evaluation by teachers throughout the planning and implementation stages of teaching, including lesson planning, and efforts to assess the students' circumstances. In conclusion, enhancing the quality of learning is contingent not only upon the efforts of teachers but also necessitates support from various factors, such as teacher competence, adequate facilities and infrastructure, and a conducive learning environment.